THE CREATIVE THINKING ABILITY IN ELEMENTARY SCHOOL MATHEMATICS PROBLEM SOLVING - Ika Silfiana Arifatul Khoiriyah; Kartika Yuni Purwanti (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The creative Thinking Ability in Elementary School Mathematics Problem Solving. The purpose of this research is how to know the quality of learning used and how to find out the creative thinking ability in student problem solving. The subjects of this classroom action research were all fourth grade students of SDN Candirejo 01, West Ungaran District, Semarang Regency, 2020/2021 academic year. This research is a qualitative research. The results of this research indicate that 1) The learning quality shows good; 2) The creative thinking ability in solving mathematical problems is analyzed by paying attention to 3 criteria, such as fluency, flexibility, and novelty. Based on the discussion that has been done by researchers on 10 research subjects.